PENGARUH DOSIS ZPT DAN WAKTU PERENDAMAN TERHADAP PEMBIBITAN TANAMAN KELAPA GENJAH ENTOG KEBUMEN - Fida Fitriana Alkhofifah; Umi Barokah (Yayasan Nusantara Hasana Berdikari, 2025)
This study aimed to determine the effect of plant growth regulator dosage and soaking duration on the early growth of Entog Kebumen dwarf coconut seedlings. Although this variety has strong potential as a local commodity, it often faces challenges during the germination and early shoot development stages. A factorial Randomized Block Design (RBD) was used, involving three plant growth regulator dosages (10, 15, and 20 ml/L) and three soaking durations (1, 2, and 3 hours). The results showed that the treatment combinations did not significantly affect the shoot emergence time or shoot height. In contrast, a high plant growth regulator dose (20 ml/L) tended to inhibit shoot emergence and other vegetative parameters such as stem girth, leaf length, and leaf width, although it increased the number of leaves. The best performance was found in the treatment with 10 ml/L plant growth regulator and 3 hours of soaking (D1W3), which resulted in a shoot emergence time of 23.72 days after soaking, shoot height of 56.62 cm, stem girth of 6.33 cm, 2.27 leaves, leaf length of 39.91 cm, and leaf width of 7.89 cm. Therefore, appropriate plant growth regulator dosage and soaking time are essential to support optimal seedling growth.